(untitled) (Global Scientific Review, 2023)
Currently, in many developed countries, the digital economy and the factors of their development have a significant impact, at the same time, the digital economy plays a necessary role in the life of society. In this article, you can find answers to questions about the digital economy, such as "What is the digital economy?", "Tasks and goals of the digital economy", "Obstacles of the digital economy in the development of Uzbekistan"